Yellowjackets. Season two [videorecording (DVD)] - Lyle, Ashley, 1980-; Nickerson, Bart, 1978- (Showtime, 2023)
The Yellowjackets barely made it through summer in the woods, but now as winter begins to bite, we'll see if hunger and desperation turn into full-on psychosis. While there may or may not be a dark and powerful force inhabiting the wilderness, their survival could depend upon what they choose to believe. Meanwhile, twenty-five years later, each survivor must ask themselves Is the darkness coming for them, or is it coming from them?